A phase 1, randomized study to evaluate safety, tolerability, and pharmacokinetics of GDC-3280, a potential novel anti-fibrotic small molecule, in healthy subjects. (August 2021) - Cheung, Dorothy; Fong, Alice; Ding, Han Ting; Cabanski, Christopher R.; Wang, Jianshuang; Chen, Yuan; Bush, Jim; Harris, Jeffrey M.; Pan, Lin
Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive lung disease. Although anti-fibrotic treatments, such as pirfenidone, are available that reduce the rate of disease progression, these medications have limitations in tolerability, and IPF patients still have poor prognoses. GDC-3280, an orally available small molecule that was designed to improve upon pirfenidone's activity, has anti-fibrotic activity in animal models. This first-in-human, phase 1 trial evaluated GDC-3280 to determine its safety, tolerability, and pharmacokinetics (PK). Methods: Single and multiple ascending-doses of GDC-3280 were administered to healthy volunteers in two parts. Part A consisted of 6 treatment groups, each receiving a single, oral dose of GDC-3280 (25–1600 mg) or placebo in the fasted state. Part A also assessed the effect of food and coadministration of a proton pump inhibitor (rabeprazole) on the tolerability and PK of single doses of 400- and 800-mg GDC-3280. Part B consisted of 3 treatment groups who received either 200- or 275-mg GDC-3280 twice daily or 525-mg once daily after a low-fat meal for 7 days. The trial monitored treatment-emergent adverse events (TEAEs) and assessed the pharmacokinetics of GDC-3280 in blood and urine samples. Results: Fifty-six subjects (42 GDC-3280, 14 placebo) in Part A and 24 subjects (18 GDC-3280, 6 placebo) in Part B received treatment. No deaths, serious adverse events, or dose-limiting adverse events occurred, and no subjects withdrew due to a TEAE. In both Parts A and B, most TEAEs were mild. The most frequent TEAEs in Part A were headache and nausea. TEAEs occurred more often when GDC-3280 was administered with food. Pretreatment and coadministration with rabeprazole had no effect on GDC-3280 tolerability. In Part B, the most frequent TEAEs were nausea, dizziness, nasal congestion, and cough. Transient, treatment-related increases in serum creatinine occurred at doses greater than 400 mg in Part A (12%–18% from baseline) and after multiple doses in each group in Part B (20%–34% from baseline). GDC-3280 was generally readily absorbed with a median tmax < 4.0 h following single- or repeat-dose oral administration. In Part A, less-than-dose-proportional increases in systemic exposure occurred, and in Part B, dose-proportional increases occurred within the dose range tested. At doses of 200 mg or lower, more than 50%–70% of orally administered doses were recovered in urine as unchanged GDC-3280 when subjects received a single dose of GDC-3280, suggesting renal excretion is one of the major routes of elimination. Administration of single doses of 400- and 800-mg GDC-3280 after a meal caused statistically significant increases in exposure due to increased rates of absorption compared to the fasted state. Pretreatment and coadministration of rabeprazole dosing led to decreases in exposure compared to GDC-3280 alone, indicating a weak drug-drug interaction. Following repeat dose administration, steady-state plasma concentrations of GDC-3280 were achieved within 2 days with an apparent terminal half-life (t1/2 ) between 5 and 6 h. Conclusions: Single and multiple doses of GDC-3280 were generally well tolerated, with acceptable safety and pharmacokinetic profiles that support twice-daily, oral administration with food in future clinical trials.